Flame-retardant bending-resistant cable and preparation method thereof
Through the specific composition of polymer substrate and modified filler, combined with the electronic accelerator radiation crosslinking technology, the shortcomings of the cables on the water photovoltaic system in terms of flame retardancy and bending resistance are solved, and the comprehensive performance of the cable is significantly improved to meet the needs of the cable. The harsh environmental demands of water photovoltaic systems.
Patent Information
- Application Number
- CN202411514866.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing water photovoltaic system cables have shortcomings in flame retardancy, bending resistance, tensile strength, waterproof performance, corrosion resistance and temperature adaptability, resulting in fire spread, mechanical performance deterioration, electrical failure and reduced reliability.
Using specific polymer substrates and modified fillers, the insulation and sheathing materials are wrapped by an extruder, and irradiated crosslinking is used to form flame-retardant and bending-resistant cables, which improves the tensile strength and breaking extension of the cable. Long-term, bending resistance and salt spray resistance.
It significantly improves the flame retardancy, bending resistance, tensile strength and salt spray resistance of the cable, extends the service life and safety of the cable, and meets the harsh environmental needs of the water photovoltaic system.
Smart Images

Figure BDA0005106425060000141 
Figure BDA0005106425060000151
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cables, and in particular relates to a flame-retardant and bend-resistant cable and a preparation method thereof. Background Art
[0002] Floating photovoltaic power stations refer to photovoltaic systems installed on the water surface, which can make solar panels float on the water surface, thereby using the water surface space to generate solar power. This type of photovoltaic power station is usually built on water bodies such as lakes, reservoirs, waters formed by abandoned coal mining subsidence areas, and even oceans.
[0003] In the prior art, the cables used in water photovoltaic systems have the following defects: 1. Insufficient flame retardancy: Water photovoltaic power stations are usually located in open waters. Once a cable fails and causes a fire, the fire may spread rapidly due to the lack of effective fire-fighting means around. Therefore, the flame retardancy of the cable is particularly important. 2. Poor bending resistance: During installation and maintenance, the cable may experience multiple bends. Due to the particularity of the water environment, such as wave movement, wind influence, etc., the cable also needs to withstand certain bending stress in daily use. If the cable does not have good bending resistance, it is easy to cause the internal conductor to break or the insulation layer to be damaged. 3. Insufficient tensile strength: When laying over a long distance or crossing obstacles, the cable may be affected by tensile stress. In addition, factors such as water flow and wind force may also cause the cable to be subjected to tensile force, especially when the cable is not fully fixed. 4. Waterproof performance: Even if the cable is not directly immersed in water, high humidity environment and occasional water splashes may affect the electrical performance of the cable. Therefore, the cable needs to have good waterproof performance to prevent moisture intrusion from causing short circuits or other electrical failures. 5. Corrosion resistance: Salt and microorganisms in the water may corrode the metal parts of the cable, especially the joints, which will reduce the reliability and service life of the cable. 6. Temperature adaptability: The temperature difference on the water varies greatly. The cable needs to be able to adapt to extreme temperature changes from low temperature to high temperature while maintaining its physical and electrical properties.
[0004] In conventional photovoltaic cable materials, a large amount of polyethylene is usually added to the polymer matrix. When these materials are used in offshore floating photovoltaic systems, the cables will experience frequent swaying and vibration due to the influence of sea breeze. This long-term dynamic load will cause fatigue in local areas of the cable, which will cause deterioration of mechanical properties and may even cause the cable to crack.
[0005] Therefore, there is an urgent need for a flame-retardant and bend-resistant cable and a preparation method thereof. Summary of the invention
[0006] The object of the present invention is to provide a flame-retardant and bend-resistant cable and a preparation method thereof.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] A method for preparing a flame-retardant and bend-resistant cable, the method comprising the following steps:
[0009] (1) Extruding the insulating material through an extruder I and wrapping it on the conductor to form an insulating layer;
[0010] (2) Extruding the sheath material through an extruder II and wrapping it on the insulation layer to form an outer sheath layer to obtain a prefabricated cable;
[0011] (3) using an electron accelerator with an energy of 2-2.3 MeV, a beam current of 20-30 mA, and a scanning width of 120 cm to irradiate and cross-link the cable to obtain a flame-retardant and bend-resistant cable;
[0012] The insulating material and the sheath material are both flame-resistant and bend-resistant cable materials, and the flame-resistant and bend-resistant cable materials are both flame-resistant and bend-resistant cable materials, and the flame-resistant and bend-resistant cable materials include the following components in parts by weight: 100 parts of polymer matrix, 10-15 parts of compatibilizer, 80-90 parts of halogen-free flame retardant, 2-4 parts of co-crosslinking agent, 3-5 parts of antioxidant, 2-5 parts of modified filler, 1-3 parts of crosslinking sensitizer and 3-5 parts of lubricant;
[0013] The polymer matrix comprises the following components in parts by weight: 30-35 parts of ethylene-vinyl acetate copolymer, 3-8 parts of ethylene-methyl methacrylate copolymer, 21-25 parts of modified acrylic rubber, 10-14 parts of polyphenylene ether resin, and 15-19 parts of ethylene acrylic rubber.
[0014] The environment of the water photovoltaic power station is relatively harsh, and higher requirements are placed on the tensile strength and elongation at break of the cable. The cable materials on the market cannot meet the needs of customers. The present invention mixes multiple polymers to obtain a polymer substrate with a specific composition, and the tensile strength and elongation at break of the cable can be improved through the synergistic effect between the polymers.
[0015] Further, the ethylene-vinyl acetate copolymer comprises ethylene-vinyl acetate copolymer I, ethylene-vinyl acetate copolymer II and ethylene-vinyl acetate copolymer III in a weight ratio of 1: (1.3-1.6): (0.5-0.7); the vinyl acetate content of ethylene-vinyl acetate copolymer I is 40wt%, and the melt index is 52g / 10min (190℃ / 2.16kg); the brand name is ALADDIN / Aladdin, and the product model is P101486. The vinyl acetate content of ethylene-vinyl acetate copolymer II is 19wt%, and the melt index is 400g / 10min (190℃ / 2.16kg), the brand name is ALADDIN / Aladdin, and the product model is P301629; the vinyl acetate content of ethylene-vinyl acetate copolymer III is 28.0wt%, and the melt index is 25g / 10min (190℃ / 2.16kg), the brand name is ALADDIN / Aladdin, and the product model is P489072.
[0016] Ethylene acrylic rubber, brand: DuPont, USA, model VamacUltraDX.
[0017] Polyphenylene ether resin, brand: Japan Asahi Kasei XYRON TM , model PPES202A.
[0018] Ethylene-methyl methacrylate copolymer, brand: Japan Sumitomo, model WH303-F.
[0019] Furthermore, the preparation method of the modified acrylic rubber comprises the following steps: by weight, 20 parts of acrylic rubber, 27-30 parts of xylene, and 4.7-5.2 parts of ethyl methacrylate are mixed, and stirred at 100-110° C. for 4-6 hours; 16-18 parts of polyisoprene are added, and stirred at 150-155° C. for 2-3 hours; 4-4.5 parts of maleic anhydride, 3.2-3.6 parts of vinyltrimethoxysilane and 2-2.5 parts of triallyl isocyanurate are added, and stirred at 172-175° C. for 2-3 hours, and xylene is removed by reduced pressure rotary evaporation to obtain the modified acrylic rubber.
[0020] Polyisoprene was purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd., with a molecular weight of 50,000 and is a colorless liquid.
[0021] The cables of the water photovoltaic system need to be bent many times during installation, maintenance or adjustment, especially when the cables are connected to solar panels with adjustable angles, and the wave movement of the water body will cause the cables to bear additional bending stress, especially in open waters with large winds and waves. The present invention can improve the bending resistance of the cable by modifying the acrylic rubber. After 2000 swing tests, there is no stress whitening phenomenon. The introduction of polyisoprene into the modified acrylic rubber can improve the flexibility of the material and make it less prone to breakage when repeatedly bent. Maleic anhydride can react with the active groups in the acrylic rubber to form new chemical bonds; triallyl isocyanurate can promote the formation of a three-dimensional network structure inside the material at high temperature, increase its cross-linking density, and the modified acrylic rubber has better compatibility with the other components in the system, forming a tighter cross-linking, thereby enhancing the mechanical strength and bending resistance of the cable material.
[0022] Furthermore, the preparation method of the modified filler comprises the following steps:
[0023] (1) mixing nano silicon dioxide, nano zinc oxide and nano dysprosium oxide to obtain a mixed filler;
[0024] (2) uniformly mixing a mixed filler, a silane coupling agent KH570, anhydrous ethanol and deionized water in a weight ratio of 1: (0.1-0.2): (15-17): (2-4), heating to 70-75° C. for reaction for 2-3 hours, centrifuging, washing and drying to obtain a silane-modified filler;
[0025] (3) SEBS-maleic anhydride copolymer, silane modified filler and cyclohexane in a weight ratio of 1: (1.2-1.4): (15-17) are mixed, stirred and ultrasonically treated for 40-50 minutes until uniformly dispersed, and then dicyclohexylcarbodiimide is added, the temperature is raised to 80-85° C. and reacted for 25-30 hours, the cyclohexane is removed, and the mixture is washed and dried to obtain a modified filler.
[0026] Furthermore, the weight ratio of nano silicon dioxide, nano zinc oxide and nano dysprosium oxide is 1:(1.3-1.6):(0.2-0.4).
[0027] Furthermore, the particle size of nano-silicon dioxide is 15-20nm and the specific surface area is 200-250m 2 / g; the particle size of nano zinc oxide is 30-50nm, and the specific surface area is 15-30m 2 / g; the particle size of nano-dysprosium oxide is 30-50nm, and the specific surface area is 20m 2 / g. Beijing Dekedaojin Technology Co., Ltd.
[0028] The salt spray in the marine environment is highly corrosive to the metal parts of the cable. The anti-salt spray test can verify whether the cable has sufficient anti-corrosion ability to ensure that the cable can still maintain its electrical and mechanical properties when exposed to the salt spray environment for a long time. The present invention attempts to improve the anti-salt spray property of the cable by adding fillers, but the effect is not good. By modifying the fillers, the anti-salt spray property of the cable can be significantly improved. Nano silicon dioxide, nano zinc oxide, etc. have good corrosion resistance. The modified nano silicon dioxide, nano zinc oxide and nano dysprosium oxide are mixed in a specific proportion, have a high specific surface area and good dispersibility, and can improve the mechanical properties and corrosion resistance of the composite material; SEBS-maleic anhydride copolymer, silane modified filler and cyclohexane are mixed, and dicyclohexylcarbodiimide is added to promote the cross-linking reaction between SEBS-maleic anhydride copolymer and modified filler to form a more stable three-dimensional network structure. The modified filler reduces the chance of corrosive substances in salt spray penetrating into the cable by enhancing the sealing performance of the material, thereby improving the anti-salt spray property of the cable material.
[0029] And when using modified fillers with specific particle sizes and ethylene-vinyl acetate copolymers with specific proportions, the tensile strength and elongation at break of the cable after immersion in NaCl solution can be improved, and the life and safety of the cable at sea can be enhanced. This is mainly because the modified fillers with specific particle sizes can form a stronger bond with the ethylene-vinyl acetate copolymer matrix with a specific proportion through the surface modifier, reducing interface defects and improving the overall mechanical properties of the material.
[0030] Furthermore, the added amount of dicyclohexylcarbodiimide accounts for 10-13% by weight of the SEBS-maleic anhydride copolymer.
[0031] SEBS-maleic anhydride copolymer, brand: American Kraton, model: SEBS FG1901GT.
[0032] Furthermore, the auxiliary cross-linking agent is triallyl isocyanurate.
[0033] Furthermore, the antioxidant is at least one of antioxidant 300, antioxidant 1076, antioxidant AT-10, and antioxidant DLTP.
[0034] Furthermore, the cross-linking sensitizer is selected from one of trimethylolpropane trimethacrylate and triallyl isocyanurate.
[0035] Furthermore, the lubricant consists of polyethylene wax, stearic acid and ethylene bisstearamide in a weight ratio of (2.7-3.1):1:(1.2-1.6).
[0036] Furthermore, the compatibilizer is one or a mixture of two or more of polyethylene grafted maleic anhydride, ethylene-octene copolymer grafted maleic anhydride, and ethylene-vinyl acetate grafted maleic anhydride.
[0037] Furthermore, the halogen-free flame retardant is aminosilane-modified magnesium hydroxide and aminosilane-modified aluminum hydroxide in a weight ratio of 1:(0.3-0.5).
[0038] Aminosilane modified magnesium hydroxide, manufacturer: Martin, Germany, brand H5IV. Aminosilane modified aluminum hydroxide, manufacturer: Martin, Germany, brand Martin(R) OL-104I.
[0039] The present invention also provides a flame-retardant and bend-resistant cable prepared by the preparation method.
[0040] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0041] 1. The present invention obtains a polymer matrix of a specific composition by mixing multiple polymers. The tensile strength and elongation at break of the cable can be improved through the synergistic effect between the polymers.
[0042] 2. The present invention can improve the bending resistance of the cable by modifying the acrylic rubber. After 2000 swing tests, there is no stress whitening phenomenon.
[0043] 3. The present invention can significantly improve the salt spray resistance of the cable by modifying the filler.
[0044] 4. When modified fillers with specific particle sizes and ethylene-vinyl acetate copolymers with specific proportions are used, the tensile strength and elongation at break of the cable after immersion in NaCl solution can be improved, thereby enhancing the service life and safety of the cable when used at sea. DETAILED DESCRIPTION
[0045] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0046] The raw materials used in the following examples of the present invention are all commercially available products:
[0047] Ethylene acrylic rubber, brand: DuPont, USA, model VamacUltraDX.
[0048] Polyphenylene ether resin, brand: Japan Asahi Kasei XYRON TM , model PPES202A.
[0049] Ethylene-methyl methacrylate copolymer, brand: Japan Sumitomo, model WH303-F.
[0050] Polyisoprene was purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd., with a molecular weight of 50,000 and is a colorless liquid.
[0051] Aminosilane modified magnesium hydroxide, manufacturer: Martin, Germany, brand H5IV. Aminosilane modified aluminum hydroxide, manufacturer: Martin, Germany, brand Martin(R) OL-104I.
[0052] SEBS-maleic anhydride copolymer, brand: American Kraton, model: SEBS FG1901GT.
[0053] Triallyl isocyanurate, CAS: 1025-15-6.
[0054] Trimethylolpropane trimethacrylate, CAS: 15625-89-5; McLean, product number: T834479.
[0055] Polyethylene wax, Ninghai Boer Chemical Co., Ltd., Polyethylene wax BR-101.
[0056] Ethylene bisstearamide, CAS No. 110-30-5.
[0057] Polyethylene grafted with maleic anhydride, CAS No.: 9006-26-2, Maclean, Product No. P875047.
[0058] Example 1
[0059] This embodiment provides a flame-retardant and bend-resistant cable, and a preparation method thereof comprises the following steps:
[0060] (1) Extruding the insulating material through an extruder I and wrapping it on the conductor to form an insulating layer;
[0061] (2) Extruding the sheath material through an extruder II and wrapping it on the insulation layer to form an outer sheath layer to obtain a prefabricated cable;
[0062] (3) using an electron accelerator with an energy of 2.2 MeV, a beam current of 25 mA, and a scanning width of 120 cm to irradiate and cross-link the cable to obtain a flame-retardant and bend-resistant cable;
[0063] The insulating material and the sheath material are both flame-resistant and bend-resistant cable materials, and the flame-resistant and bend-resistant cable materials include the following components in parts by weight: 100 parts of polymer matrix, 12 parts of compatibilizer, 84 parts of halogen-free flame retardant, 3 parts of co-crosslinking agent, 4 parts of antioxidant, 4 parts of modified filler, 2 parts of crosslinking sensitizer and 4 parts of lubricant;
[0064] The auxiliary cross-linking agent is triallyl isocyanurate. The antioxidant is antioxidant 300. The cross-linking sensitizer is trimethylolpropane trimethacrylate. The lubricant is composed of polyethylene wax, stearic acid and ethylene bisstearamide in a weight ratio of 3:1:1.5. The compatibilizer is polyethylene grafted maleic anhydride. The halogen-free flame retardant is aminosilane-modified magnesium hydroxide and aminosilane-modified aluminum hydroxide in a weight ratio of 1:0.4.
[0065] The polymer matrix includes the following components in parts by weight: 32 parts of ethylene-vinyl acetate copolymer, 5 parts of ethylene-methyl methacrylate copolymer, 22 parts of modified acrylic rubber, 12 parts of polyphenylene ether resin, and 17 parts of ethylene acrylic rubber.
[0066] The ethylene-vinyl acetate copolymer includes ethylene-vinyl acetate copolymer I, ethylene-vinyl acetate copolymer II and ethylene-vinyl acetate copolymer III in a weight ratio of 1:1.5:0.6; the vinyl acetate content of ethylene-vinyl acetate copolymer I is 40wt%, and the melt index is 52g / 10min (190℃ / 2.16kg); the brand name is ALADDIN / Aladdin, and the product model is P101486. The vinyl acetate content of ethylene-vinyl acetate copolymer II is 19wt%, and the melt index is 400g / 10min (190℃ / 2.16kg), the brand name is ALADDIN / Aladdin, and the product model is P301629; the vinyl acetate content of ethylene-vinyl acetate copolymer III is 28.0wt%, and the melt index is 25g / 10min (190℃ / 2.16kg), the brand name is ALADDIN / Aladdin, and the product model is P489072.
[0067] The preparation method of the modified acrylic rubber comprises the following steps: by weight, 20 parts of acrylic rubber, 28 parts of xylene and 5 parts of ethyl methacrylate are mixed, and the mixture is stirred at 105° C. for 5 hours; 17 parts of polyisoprene are added, and the mixture is stirred at 152° C. for 2.5 hours; 4.2 parts of maleic anhydride, 3.4 parts of vinyltrimethoxysilane and 2.2 parts of triallyl isocyanurate are added, the mixture is stirred at 173° C. for 2.5 hours, and the xylene is removed by vacuum rotary evaporation to obtain the modified acrylic rubber.
[0068] The preparation method of the modified filler comprises the following steps:
[0069] (1) mixing nano silicon dioxide, nano zinc oxide and nano dysprosium oxide in a weight ratio of 1:1.5:0.3 to obtain a mixed filler;
[0070] (2) mixing a mixed filler, a silane coupling agent KH570, anhydrous ethanol and deionized water in a weight ratio of 1:0.15:16:3, heating to 72°C for reaction for 2.5 hours, centrifuging, washing and drying to obtain a silane-modified filler;
[0071] (3) SEBS-maleic anhydride copolymer, silane-modified filler and cyclohexane in a weight ratio of 1:1.3:16 are mixed, stirred and ultrasonically treated for 45 minutes until uniformly dispersed, and then dicyclohexylcarbodiimide is added, and the amount of dicyclohexylcarbodiimide added is 12% of the weight of the SEBS-maleic anhydride copolymer. The temperature is raised to 82°C and reacted for 27 hours. The cyclohexane is removed, and the mixture is washed and dried to obtain a modified filler.
[0072] The particle size of nano-silicon dioxide is 15-20nm and the specific surface area is 200-250m 2 / g; the particle size of nano zinc oxide is 30-50nm, and the specific surface area is 15-30m 2 / g; the particle size of nano-dysprosium oxide is 30-50nm, and the specific surface area is 20m 2 / g. Beijing Dekedaojin Technology Co., Ltd.
[0073] The preparation method of the insulating material and the sheath material comprises the following steps: mixing the components to obtain a premix; adding the premix to an internal mixer for mixing, mixing to 150° C. and discharging to obtain a mixture; extruding the mixture through an extruder for granulation, wherein the extruder is a twin-screw extruder-single-screw extruder unit, wherein the length-to-diameter ratio L / D of the twin-screw extruder is 44, and the temperature of the twin-screw extruder is set as follows: the temperature of the first zone is 130° C., the temperature of the second zone is 145° C., the temperature of the third zone is 150° C., the temperature of the fourth zone is 160° C., the temperature of the fifth zone is 160° C., the temperature of the sixth zone is 155° C., and the temperature of the seventh zone is 155° C.; the temperature of the single-screw extruder is set as follows: the temperature of the feeding section is 110° C., the compression section is 145° C., and the homogenization section is 150° C.
[0074] Example 2
[0075] This embodiment provides a flame-retardant and bend-resistant cable, and a preparation method thereof comprises the following steps:
[0076] (1) Extruding the insulating material through an extruder I and wrapping it on the conductor to form an insulating layer;
[0077] (2) Extruding the sheath material through an extruder II and wrapping it on the insulation layer to form an outer sheath layer to obtain a prefabricated cable;
[0078] (3) using an electron accelerator with an energy of 2 MeV, a beam current of 30 mA, and a scanning width of 120 cm to irradiate and cross-link the cable to obtain a flame-retardant and bend-resistant cable;
[0079] The insulating material and the sheath material are both flame-resistant and bend-resistant cable materials, and the flame-resistant and bend-resistant cable materials include the following components in parts by weight: 100 parts of polymer matrix, 10 parts of compatibilizer, 90 parts of halogen-free flame retardant, 2 parts of co-crosslinking agent, 5 parts of antioxidant, 5 parts of modified filler, 1 part of crosslinking sensitizer and 5 parts of lubricant;
[0080] The auxiliary cross-linking agent is triallyl isocyanurate. The antioxidant is antioxidant 1076. The cross-linking sensitizer is triallyl isocyanurate. The lubricant is composed of polyethylene wax, stearic acid and ethylene bis stearamide in a weight ratio of 2.7:1:1.6. The compatibilizer is polyethylene grafted maleic anhydride. The halogen-free flame retardant is aminosilane-modified magnesium hydroxide and aminosilane-modified aluminum hydroxide in a weight ratio of 1:0.3.
[0081] The polymer matrix includes the following components in parts by weight: 30 parts of ethylene-vinyl acetate copolymer, 8 parts of ethylene-methyl methacrylate copolymer, 21 parts of modified acrylic rubber, 14 parts of polyphenylene ether resin, and 15 parts of ethylene acrylic rubber.
[0082] The ethylene-vinyl acetate copolymer includes ethylene-vinyl acetate copolymer I, ethylene-vinyl acetate copolymer II and ethylene-vinyl acetate copolymer III in a weight ratio of 1:1.3:0.5; the vinyl acetate content of ethylene-vinyl acetate copolymer I is 40wt%, the melt index is 52g / 10min (190℃ / 2.16kg); the brand name is ALADDIN / Aladdin, and the product model is P101486. The vinyl acetate content of ethylene-vinyl acetate copolymer II is 19wt%, the melt index is 400g / 10min (190℃ / 2.16kg), the brand name is ALADDIN / Aladdin, and the product model is P301629; the vinyl acetate content of ethylene-vinyl acetate copolymer III is 28.0wt%, the melt index is 25g / 10min (190℃ / 2.16kg), the brand name is ALADDIN / Aladdin, and the product model is P489072.
[0083] The preparation method of the modified acrylic rubber comprises the following steps: by weight, 20 parts of acrylic rubber, 27 parts of xylene and 5.2 parts of ethyl methacrylate are mixed, and the mixture is stirred at 100° C. for 6 hours; 16 parts of polyisoprene are added, and the mixture is stirred at 155° C. for 2 hours; 4.5 parts of maleic anhydride, 3.2 parts of vinyl trimethoxysilane and 2.5 parts of triallyl isocyanurate are added, the mixture is stirred at 172° C. for 3 hours, and the xylene is removed by vacuum rotary evaporation to obtain the modified acrylic rubber.
[0084] The preparation method of the modified filler comprises the following steps:
[0085] (1) mixing nano silicon dioxide, nano zinc oxide and nano dysprosium oxide in a weight ratio of 1:1.3:0.2 to obtain a mixed filler;
[0086] (2) mixing a mixed filler, a silane coupling agent KH570, anhydrous ethanol and deionized water in a weight ratio of 1:0.2:15:4, heating to 70°C for reaction for 3 hours, centrifuging, washing and drying to obtain a silane-modified filler;
[0087] (3) SEBS-maleic anhydride copolymer, silane-modified filler and cyclohexane in a weight ratio of 1:1.2:15 are mixed, stirred and ultrasonically treated for 50 minutes until uniformly dispersed, and then dicyclohexylcarbodiimide is added, and the amount of dicyclohexylcarbodiimide added is 10% of the weight of the SEBS-maleic anhydride copolymer. The temperature is raised to 85°C and reacted for 25 hours. The cyclohexane is removed, and the mixture is washed and dried to obtain a modified filler.
[0088] The particle size of nano-silicon dioxide is 15-20nm and the specific surface area is 200-250m 2 / g; the particle size of nano zinc oxide is 30-50nm, and the specific surface area is 15-30m 2 / g; the particle size of nano-dysprosium oxide is 30-50nm, and the specific surface area is 20m 2 / g. Beijing Dekedaojin Technology Co., Ltd.
[0089] The preparation method of the insulating material and the sheath material comprises the following steps: mixing the components to obtain a premix; adding the premix to an internal mixer for mixing, mixing to 150° C. and discharging to obtain a mixture; extruding the mixture through an extruder for granulation, wherein the extruder is a twin-screw extruder-single-screw extruder unit, wherein the length-to-diameter ratio L / D of the twin-screw extruder is 44, and the temperature of the twin-screw extruder is set as follows: the temperature of the first zone is 130° C., the temperature of the second zone is 145° C., the temperature of the third zone is 150° C., the temperature of the fourth zone is 160° C., the temperature of the fifth zone is 160° C., the temperature of the sixth zone is 155° C., and the temperature of the seventh zone is 155° C.; the temperature of the single-screw extruder is set as follows: the temperature of the feeding section is 110° C., the compression section is 145° C., and the homogenization section is 150° C.
[0090] Comparative Example 1
[0091] The difference between this comparative example and Example 1 is that the composition of the polymer substrate is different.
[0092] The polymer substrate comprises the following components in parts by weight: 25 parts of ethylene-vinyl acetate copolymer, 16 parts of ethylene-methyl methacrylate copolymer, 16 parts of modified acrylic rubber, 21 parts of polyphenylene ether resin, and 10 parts of ethylene acrylic rubber.
[0093] Comparative Example 2
[0094] The difference between this comparative example and Example 1 is that the composition of the polymer substrate is different.
[0095] The polymer substrate comprises the following components in parts by weight: 37 parts of ethylene-vinyl acetate copolymer, 1 part of ethylene-methyl methacrylate copolymer, 26 parts of modified acrylic rubber, 2 parts of polyphenylene ether resin, and 22 parts of ethylene acrylic rubber.
[0096] Comparative Example 3
[0097] The difference between this comparative example and Example 1 is that the ethylene-vinyl acetate copolymer comprises ethylene-vinyl acetate copolymer I, ethylene-vinyl acetate copolymer II and ethylene-vinyl acetate copolymer III in a weight ratio of 1:1:1; the vinyl acetate content of ethylene-vinyl acetate copolymer I is 40wt%, and the melt index is 52g / 10min (190℃ / 2.16kg); the brand name is ALADDIN / Aladdin, and the product model is P101486. The vinyl acetate content of ethylene-vinyl acetate copolymer II is 19wt%, and the melt index is 400g / 10min (190℃ / 2.16kg), the brand name is ALADDIN / Aladdin, and the product model is P301629; the vinyl acetate content of ethylene-vinyl acetate copolymer III is 28.0wt%, and the melt index is 25g / 10min (190℃ / 2.16kg), the brand name is ALADDIN / Aladdin, and the product model is P489072.
[0098] Comparative Example 4
[0099] The difference between this comparative example and Example 1 is that the acrylic rubber is not modified.
[0100] Comparative Example 5
[0101] The difference between this comparative example and Example 1 is that nano silicon dioxide, nano zinc oxide and nano dysprosium oxide are mixed in a weight ratio of 1:1:1.
[0102] Comparative Example 6
[0103] The difference between this comparative example and Example 1 is that the particle size of the nano-silicon dioxide is 40-60nm, and the specific surface area is 120-180m 2 / g; the particle size of nano zinc oxide is 70-90nm, and the specific surface area is 5-10m 2 / g; the particle size of nano-dysprosium oxide is 80-100nm, and the specific surface area is 13m 2 / g. Beijing Dekedaojin Technology Co., Ltd.
[0104] Comparative Example 6
[0105] The difference between this comparative example and Example 1 is:
[0106] The preparation method of the modified filler comprises the following steps:
[0107] (1) mixing nano silicon dioxide, nano zinc oxide and nano dysprosium oxide in a weight ratio of 1:1.5:0.3 to obtain a mixed filler;
[0108] (2) Mix the mixed filler, silane coupling agent KH570, anhydrous ethanol and deionized water in a weight ratio of 1:0.15:16:3, heat to 72°C for reaction for 2.5 hours, centrifuge, wash and dry to obtain a modified filler.
[0109] The particle size of nano-silicon dioxide is 15-20nm and the specific surface area is 200-250m 2 / g; the particle size of nano zinc oxide is 30-50nm, and the specific surface area is 15-30m 2 / g; the particle size of nano-dysprosium oxide is 30-50nm, and the specific surface area is 20m 2 / g. Beijing Dekedaojin Technology Co., Ltd.
[0110] Comparative Example 8
[0111] The difference between this comparative example and Example 1 is:
[0112] The ethylene-vinyl acetate copolymer includes ethylene-vinyl acetate copolymer I, ethylene-vinyl acetate copolymer II and ethylene-vinyl acetate copolymer III in a weight ratio of 1:1.5:0.6; the vinyl acetate content of ethylene-vinyl acetate copolymer I is 26wt%, and the melt index is 7.5g / 10min (test method ASTM D1238); the brand name is Taiwan Formosa Plastics, and the product model is 7470M. The vinyl acetate content of ethylene-vinyl acetate copolymer II is 12wt%, and the melt index is 8g / 10min (190℃ / 2.16kg), the brand name is McLean, and the product model is P815473; the vinyl acetate content of ethylene-vinyl acetate copolymer III is 32wt%, and the melt index is 43g / 10min (190℃ / 2.16kg), the brand name is McLean, and the product model is P815476.
[0113] Performance Testing
[0114] The flame-resistant and bend-resistant cable materials prepared in Examples 1-2 and Comparative Examples 1-8 were subjected to performance tests.
[0115] 1. Tensile strength and elongation at break: Tested in accordance with IEC60811; at the same time, the tensile strength and elongation at break were tested after immersion in 10% NaCl solution at 90℃×168h;
[0116] 2. Single vertical burning: IEC60332-1;
[0117] 3. Swing test: GB / T25087, swing 2000 times to test whether there is stress whitening.
[0118] 4. Salt spray test: refer to IEC60068-2-52, test conditions: 5% salt solution, 35℃×48h.
[0119] 5. Breakdown voltage: Tested according to the method of GB / T1408-2016;
[0120] 6. Limiting oxygen index: Tested according to the method of GB / T2406.1-2008.
[0121] Table 1 Performance test results
[0122]
[0123]
[0124] It can be seen from the above performance test results that the flame-retardant and bend-resistant cable materials of Examples 1-2 have excellent comprehensive performance, especially the comprehensive performance of Example 1 is the most outstanding, which is mainly due to the synergistic effect between the components.
[0125] However, the comparative examples are significantly inferior to the embodiments in the corresponding performance tests because they do not adopt the necessary technical solutions. The composition of the polymer substrates in comparative examples 1 and 2 is changed, and it can be seen from the results that the tensile strength and elongation at break of the cable decrease. The ratio of ethylene-vinyl acetate copolymer in comparative example 3 is changed, and the tensile strength and elongation at break of the cable decrease after being immersed in NaCl solution. In comparative example 4, the acrylic rubber is not modified, and the bending resistance of the cable material decreases. In comparative example 5, the composition of the filler is different, and the salt spray resistance of the cable decreases. In comparative example 6, the parameters of the filler are different, and the tensile strength and elongation at break of the cable decrease after being immersed in NaCl solution. In comparative example 7, the modification method of the filler is different, and the salt spray resistance of the cable decreases. In comparative example 8, the parameters of ethylene-vinyl acetate copolymer are different, and the tensile strength and elongation at break of the cable decrease after being immersed in NaCl solution. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.
[0126] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a flame-retardant and bend-resistant cable, characterized in that: The preparation method comprises the following steps: (1) Extruding the insulating material through an extruder I and wrapping it on the conductor to form an insulating layer; (2) Extruding the sheath material through extruder II and wrapping it on the insulation layer to form an outer sheath layer to obtain a prefabricated cable; (3) Using an electron accelerator to irradiate and cross-link the cable to obtain a flame-retardant and bend-resistant cable; The insulating material and the sheath material are both flame-resistant and bend-resistant cable materials, and the flame-resistant and bend-resistant cable materials include the following components in parts by weight: 100 parts of polymer matrix, 10-15 parts of compatibilizer, 80-90 parts of halogen-free flame retardant, 2-4 parts of co-crosslinking agent, 3-5 parts of antioxidant, 2-5 parts of modified filler, 1-3 parts of crosslinking sensitizer and 3-5 parts of lubricant; The polymer matrix comprises the following components in parts by weight: 30-35 parts of ethylene-vinyl acetate copolymer, 3-8 parts of ethylene-methyl methacrylate copolymer, 21-25 parts of modified acrylic rubber, 10-14 parts of polyphenylene ether resin, and 15-19 parts of ethylene acrylic rubber.
2. The method for preparing a flame-retardant and bend-resistant cable according to claim 1, characterized in that: The ethylene-vinyl acetate copolymer comprises ethylene-vinyl acetate copolymer I, ethylene-vinyl acetate copolymer II and ethylene-vinyl acetate copolymer III in a weight ratio of 1: (1.3-1.6): (0.5-0.7); the vinyl acetate content of ethylene-vinyl acetate copolymer I is 40wt%, and the melt index is 52g / 10min; the vinyl acetate content of ethylene-vinyl acetate copolymer II is 19wt%, and the melt index is 400g / 10min; the vinyl acetate content of ethylene-vinyl acetate copolymer III is 28.0wt%, and the melt index is 25g / 10min.
3. The method for preparing a flame-retardant and bend-resistant cable according to claim 1, characterized in that: The preparation method of the modified acrylic rubber comprises the following steps: by weight, 20 parts of acrylic rubber, 27-30 parts of xylene and 4.7-5.2 parts of ethyl methacrylate are mixed, and the mixture is stirred at 100-110° C. for 4-6 hours; 16-18 parts of polyisoprene are added, and the mixture is stirred at 150-155° C. for 2-3 hours; 4-4.5 parts of maleic anhydride, 3.2-3.6 parts of vinyl trimethoxysilane and 2-2.5 parts of triallyl isocyanurate are added, the mixture is stirred at 172-175° C. for 2-3 hours, and xylene is removed by vacuum rotary evaporation to obtain the modified acrylic rubber.
4. The method for preparing a flame-retardant and bend-resistant cable according to claim 1, characterized in that: The preparation method of the modified filler comprises the following steps: (1) mixing nano silicon dioxide, nano zinc oxide and nano dysprosium oxide to obtain a mixed filler; (2) Mixing a mixed filler, a silane coupling agent KH570, anhydrous ethanol and deionized water in a weight ratio of 1: (0.1-0.2): (15-17): (2-4) uniformly, heating to 70-75° C. to react for 2-3 hours, centrifuging, washing and drying to obtain a silane-modified filler; (3) SEBS-maleic anhydride copolymer, silane modified filler and cyclohexane in a weight ratio of 1: (1.2-1.4): (15-17) are mixed, stirred and ultrasonically treated for 40-50 min until uniformly dispersed, and then dicyclohexylcarbodiimide is added, and the temperature is raised to 80-85° C. to react for 25-30 h, and the cyclohexane is removed, washed and dried to obtain a modified filler.
5. The method for preparing a flame-retardant and bend-resistant cable according to claim 4, characterized in that: The weight ratio of nano silicon dioxide, nano zinc oxide and nano dysprosium oxide is 1: (1.3-1.6): (0.2-0.4).
6. The method for preparing a flame-retardant and bend-resistant cable according to claim 5, characterized in that: The particle size of nano-silicon dioxide is 15-20nm and the specific surface area is 200-250m 2 / g; the particle size of nano zinc oxide is 30-50nm, and the specific surface area is 15-30m 2 / g; the particle size of nano-dysprosium oxide is 30-50nm, and the specific surface area is 20m 2 / g.
7. The method for preparing a flame-retardant and bend-resistant cable according to claim 4, characterized in that: The amount of dicyclohexylcarbodiimide added is 10-13% by weight of the SEBS-maleic anhydride copolymer.
8. The method for preparing a flame-retardant and bend-resistant cable according to claim 1, characterized in that: The lubricant consists of polyethylene wax, stearic acid and ethylene bis stearamide in a weight ratio of (2.7-3.1):1:(1.2-1.6).
9. The method for preparing a flame-retardant and bend-resistant cable according to claim 1, characterized in that: The halogen-free flame retardant is aminosilane-modified magnesium hydroxide and aminosilane-modified aluminum hydroxide in a weight ratio of 1:(0.3-0.5).
10. A flame-retardant and bend-resistant cable made by the preparation method according to any one of claims 1 to 9.
Citation Information
Cited By
Tensile wear-resistant high-flexibility fluorescent cable for electric tool and preparation method thereof
CN121122813A
